Correlation of Durability Aspects of Concrete Mixes with the 28 Days Strength and Absorption Characteristics - Anand, Kamal (My University, 2014)
Concrete structures are designed so that they can satisfy requirements regarding safety, serviceability, durability and aesthetics throughout their design service life. Present design procedures regarding compressive strength required by national or international codes are predominantly based on strength principles. The durability aspect is a natural extension of the classical resistance verification where deterioration effects are normally neglected. However judging the durability by 28 days compressive strength might not give appropriate results. This is because durability is related to ingress chloride of chemical from atmosphere inside concrete. It is related more to properties of surface concrete, whereas compressive strength is a bulk concrete property. Thus there is need to relate durability performance both to the compressive strength (CS) & the parameter depicting the property of surface concrete. Initial surface absorption test (ISAT) is one such parameter. In the present work, corrosion is related to CS and ISAT. One of the major causes of deterioration of reinforced concrete structure is chloride-induced corrosion of the reinforcing steel. The magnitude of the damage is especially large in structures exposed to marine environments. The capacity of the concrete cementitious system to bind chloride ions has an important effect on the corrosion initiation of the steel reinforcement. In the recent years design is related to durability through analysis of resistance to chloride ingress. In present research work, cubes of size 150 mm x 150 mm x 150 mm and slabs of size 300 mm x 300 mm x 52mm were casted with two types of cement i.e. OPC and PPC, four water-cement ratios i.e. 0.40, 0.45, 0.50, 0.55 and admixed with 4.5% NaCl by weight of cement. Cubes are tested for compressive strength as well as (ISAT) and corrosion density is measured through Linear polarization resistance (LPR) in slabs made with admixed chloride. Chloride level does not significantly affect the compressive strength of concrete at 28 days age. It is observed that variation in corrosion current density is not systematic with water-cement ratio. Corrosion is more in OPC cement as compared to PPC. Thus blended cement performed well as compared to OPC. However it can be correlated to combination of CS & ISAT. For that model is developed through GP kernel using various parameters of ISAT and compressive strength.
M.E. (Structural Engineering)
Keywords: ISAT; Corrosion; Genetic Programming